A General Theorem in the Theory of Asymptotic Expansions as Approximations to the Finite Sample Distributions of Econometric Estimators - Phillips, P. C. B. (Econometrica, 1977)
P. C. B. Phillips, A General Theorem in the Theory of Asymptotic Expansions as Approximations to the Finite Sample Distributions of Econometric Estimators, Econometrica, Vol. 45, No. 6 (Sep., 1977), pp. 1517-1534